Effectiveness of Health Educational Program on Nurses’ Practices toward Chemotherapy-Induced Peripheral Neuropathy for Children at Hematology Center in Baghdad City - Abdel Nasser, Jamal; Hassoun, Soad (Iraqi National Journal of Nursing Specialties, 2020)
Objectives: the study aims to assess nurses’ practices toward chemotherapy-induced peripheral neuropathy (CIPN) for children at the hematology center, and to determine the effectiveness of the health education program on nurses’ practices toward CIPN, and to find out the relationships between the effectiveness of Health education program and demographic characteristics of nurses. Methodology: Use quasi-experimental design in the study (a design that divides the sample into two groups, a study group and a control group, with data collection in three stages). This study was conducted at a hematology center in Baghdad city for the period (from December 16th, 2019 to 8th May 2020), to find out the effectiveness of the health education program on nurses’ practices toward CIPN, a targeted (non-probability) sample was purposive consisting of (50 nurses) divided into two groups (25) nurses for the study group and (25) control group nurses working in the hematology center. A questionnaire was constructed as a tool to collect data and consisted of two parts: Demographic characteristics of the nursing (age, gender, years of experience in nursing, years of experience in hematology center, marital status, level of education, and Participation in training courses toward CIPN). assess of nurses’ practices towards CIPN consisting of four domains (41) checklist. Validity of the study instrument to the educational program was verified by presenting it to (11) experts, reliability of the questionnaire done by test and re-test approach on six nurses at Hematology center interval period of 21 days. Results: The study showed that a clear changing in nurses’ practices toward CIPN at hematology center, where the value (P-value =0.00) for a pre-test and a post-test I), as well as a post-test II in the study group. While a little difference changing in nurses practices, where the value (P-value =0.46) for a pre-test and a post-test I, as well as a post-test II where the value (P-value =0.46) in the study control. Recommendations: Based on the results of the mentioned study, the researcher recommends implementing this educational program in all hospitals and centers for pediatric hematology, oncology and bone marrow in Iraq